Pengaruh Dukungan Manajemen Puncak, Kemampuan Teknik Personal, Program Pendidikan Dan Pelatihan Terhadap Kinerja Sistem Informasi Akuntansi - Kadek Dian Indrayani (UNHI Press, 2022)
The purpose of this study is to determine the Effect of Top Management Support, Personal Engineering Ability, Education and Training Programs on the Performance of Accounting Information Systems. This research was conducted on all agencies in the Tabanan Regency Local Government.. primary data obtained using questionnaires. The population in this study was 5,006 employees in the Tabanan Regency Local Government Office. The sampling technique used in purposive sampling with 63 respondents. The analysis technique used is Multiple Linear Regression. Result show that the Influence of Top Management Support, Personal Ability, Education and Training Programs has a positive and significant effect on the Performance of Accounting Information Systems.